Unique Keywords Found in the Titles of YouTube Beauty and Fashion Videos - Lintang Larasati; Rio Rini Diah Moehkardi (Universitas Gadjah Mada, 2019)
This study analyzes the meaning of the keywords used in YouTube’s beauty and fashion videos. It attempts to identify the most frequently used unique keywords found in the titles of the videos and examine the semantic change of the keywords. For these purposes, a semantic approach was adopted. A quantitative method was used to identify the most frequently used unique keywords. Furthermore, to reveal the semantic change of the keywords, Leech’s theory (1981) of meaning, the componential analysis, and Breal’s (1900) specification of semantic change were employed. 44 most frequently used unique keywords were found on the five top rank Beauty & Fashion YouTube channels. Five of these keywords, which are ‘favorites’, ‘swatches’, ‘haul’, ‘get ready’, and ‘try on’, appeared on at least three channels. All of them have undergone semantic change. Three keywords are categorized in two types of semantic change. There are two specializations, one pejoration, one metaphor, three ameliorations, and one generalization.